Physical and emulsifying properties of pea protein: influence of combined physical modification by flaxseed gum and ultrasonic treatment - Jia Yang; Fenghong Huang; Qingde Huang; Da Ma; Yashu Chen; Dengfeng Peng; Xiao Yu; Qianchun Deng; Fang Geng (Food Science and Human Wellness, 2023)
This study characterized and compared the physical and emulsifying properties of pea protein (PP) and its modified proteins (ultrasound treated- PP (PPU), flaxseed gum (FG) treated PP (PPFG) and ultrasound treated- PPFG (PPFGU)). The results showed FG triggered the formation of loosely attached complex with PP via physical modification under gentle magnetic stirring at pH 7.0, while ultrasound played an important role in reducing protein size, increasing surface hydrophobicity and molecular fluidity onto oil-water interface. So ultrasound further enhanced the interaction of PP with FG, and produced the PPFGU complex with smaller droplet size, higher ζ-potential and lower turbidity. Further, combination of FG and ultrasound improved the physical properties of PP with higher viscosity, stiffer gels (defined as higher elastic modulus), stronger hydrophobic properties, better thermal stability, and fast protein absorption rate. Therefore, the PPFGU coarse emulsion performed highest emulsifying activity index (EAI) and emulsion stability index (ESI) that the stabilized nanoemulsion obtained smallest droplet size, higher ζ-potential, and longest storage stability. The combination of FG and ultrasonic treatment will be an effective approach to improving the emulsifying property and thermal stability of PP, which can be considered as a potential plant-based emulsifier applied in the food industry.